2004
DOI: 10.1073/pnas.0308718101
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E 2 -increased thermosensitivity of anterior hypothalamic neurons is associated with depressed inhibition

Abstract: Temperature responses of anterior hypothalamic neurons are considered key elements in the regulation of the temperature setpoint of homeotherms. We have investigated the sensitivity to warming of cultured neurons of the AH from mice with electrophysiological and immunocytochemical techniques. In control experiments, only Ϸ9% of the 3-to 5-week-old cells exhibited changes of their basic firing rate when the temperature was raised from 37°C to 40°C. This ratio was increased to 27% after the cultures were ''prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…The EP3R-like immunoreactivity is richly expressed in the rodent brain, with the highest density of EP3R receptors in the different hypothalamic nuclei involved in thermoregulation and sleep regulation (48)(49)(50). We have shown that EP3R mediates the effects of PGE 2 , a potent pyrogen, on the thermosensitivity of anterior hypothalamic neurons (51). EP3R-like immunoreactivity is also abundant in monoaminergic nuclei such as the raphe nuclei and locus ceruleus (48), where this prostanoid receptor may affect appetite and feeding through modulation of the serotonergic and noradrenergic signaling.…”
Section: Night Eating and Obesity In The Ep3r-deficient Mousementioning
confidence: 91%
“…The EP3R-like immunoreactivity is richly expressed in the rodent brain, with the highest density of EP3R receptors in the different hypothalamic nuclei involved in thermoregulation and sleep regulation (48)(49)(50). We have shown that EP3R mediates the effects of PGE 2 , a potent pyrogen, on the thermosensitivity of anterior hypothalamic neurons (51). EP3R-like immunoreactivity is also abundant in monoaminergic nuclei such as the raphe nuclei and locus ceruleus (48), where this prostanoid receptor may affect appetite and feeding through modulation of the serotonergic and noradrenergic signaling.…”
Section: Night Eating and Obesity In The Ep3r-deficient Mousementioning
confidence: 91%
“…Indeed, multiple studies show that IL-1␤, both in vivo and in vitro, can rapidly inhibit the spontaneous firing of warm-sensitive neurons (14,15), which, together with cold-sensitive and heat-insensitive POA͞AH neurons, are thought to regulate the body temperature set point (13). Because the cell-penetrating C2-ceramide mimicked the effects of IL-1␤ in vivo, we compared the effects of IL-1␤ and C2-ceramide on the activity and thermosensitivity of cultured warm-sensitive POA͞AH neurons, characterized earlier in detail (16,17). Bath application of IL-1␤ or C2-ceramide, in the presence of the PG synthesis inhibitor indomethacin (10 M), resulted in hyperpolarization and decreased the firing rate of these neurons (effects that developed within 1-2 min) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The thermosensitivity of PO/AH neurons is a plastic property both in vivo and in vitro. It has been found that the thermosensitivity can change rapidly in the presence of the pyrogens PGE2 [4] or IL-1 [5,6]. Slower changes are observed in some warm-sensitive PO/AH neurons which decrease their thermosensitivity during NREM sleep [7].…”
Section: Hypothalamic Control Of Thermoregulationmentioning
confidence: 99%
“…The question remains open as to whether all warm-sensitive PO/AH neurons have some intrinsic thermosensitivity or if they can also display thermosensitive firing that is synaptically-driven [10]. We have shown that prostaglandin E2 (PGE2), a well established endogenous pyrogen, increases the thermosensitivity and firing rates of PO/AH neurons by decreasing the frequency of IPSPs [4]. In contrast, IL-1β hyperpolarizes a different set of PO/AH neurons and reduces their thermosensitivity by increasing the frequency of IPSPs and of miniature IPSPs [5,13].…”
Section: Hypothalamic Control Of Thermoregulationmentioning
confidence: 99%